Multiple tandemly repeated binding sites for cellular nuclear factor 1 that surround the major immediate-early promoters of simian and human cytomegalovirus. - Jeang, K T (1987)
We show that the large DNA genomes of human and simian cytomegaloviruses (HCMV and SCMV, respectively) each contain multiple binding sites for purified cellular nuclear factor 1 (NF1) protein. Examination of the major immediate-early (IE) gene region in the HindIII H fragment of SCMV (Colburn) by filter binding assays showed that it competed 45-fold better than the single adenovirus type 2 binding site for NF1 protein and that it contained at least two distinct binding loci. Direct DNase I footprinting analyses of the 5' upstream locus detected at least 20 adjacent NF1-binding sites located between positions -600 and -1300 relative to the IE94 mRNA start site. DNA sequence analysis of the region revealed a conserved consensus NF1 recognition element (T)TGG(C/A)N5GCCAA embedded within each of 23 highly diverged 30-base-pair tandem repeats, together with a second downstream cluster of five consensus NF1-binding sites between positions +470 and +570 in the large first intron. Two separate NF1-binding loci were also found in the equivalent IE68 gene of HCMV(Towne) DNA, but in this case the DNA sequence and competition filter binding experiments indicated a maximum of only four to five consensus binding sites encompassing the promoter-enhancer region. In transient expression assays, neither the isolated upstream IE94 tandem repeats nor a synthetic single-copy consensus NF1-binding site acted as transcriptional cis activators or enhancers when placed adjacent to the simian virus 40 minimal early region promoter. We conclude that the large and complex 5' upstream promoter-regulatory region for the SCMV IE94 gene comprises two distinct domains. The previously described four sets of 13- to 18-base-pair interspersed repeat elements between -55 and -580 provide most of the high basal transcriptional strength, whereas the arrangement of further upstream tandemly repeated NF1-binding sites may contribute significantly to the expanded biological host range for expression of SCMV IE94 compared with HCMV IE68.